Clinical and epidemiological characteristics of pyogenic liver abscess in people 65 years or older versus people under 65: a retrospective study - Jorge Peris; Pablo Bellot; Pablo Roig; Sergio Reus; Sara Carrascosa; Gregorio González-Alcaide; José M. Palazón; José M. Ramos (BMC Geriatrics, 2017)
Abstract Background To analyse the clinical, epidemiological, microbiological and prognostic differences of pyogenic liver abscess (PLA) in older (≥ 65 years of age) versus younger patients (< 65 years). Methods Multicentre, retrospective cohort study in all patients with PLA admitted to two Spanish hospitals from January 2000 to January 2014. Cases were divided into two age groups (< 65 years and ≥65 years) for comparison of clinical, epidemiological and microbiological characteristics as well as treatment. Results Of 98 patients analysed, 40 patients were younger than 65, and 58 were aged 65 or older. Significant associations in the older group were found with female sex (adjusted odds ratio [ORa] 9.0; 95% CI 1.4, 56), non-cryptogenic origin (ORa 14.5; 95% CI 1.6, 129), absence of chronic liver disease (ORa 14; 95% CI 1.3, 155), Escherichia coli infection (ORa 7.7; 95% CI 1.03, 58), and incidence of complications (ORa 2.3; 95% CI 1.04, 5.4). Mortality was 8.2% overall, although all deaths occurred in the older group (8/58; 13.8%) (p = 0.02). Discussion Our results are in consonance with other published studies. Older patients with PLA tend to present more anomalies in the biliary tract (Kai et. al, World J Gastroenterol 18: 2948-295, 2012, Rahimian et. al, Clin Infect Dis 39:1654-9, 2004, Seeto, Medicine (Baltimore) 75:99-113, 1996, Kao et.al, Aliment Pharmacol Ther 36:467-76, 2012, Lai et. al, Gastroenterology 146:129-37, 2014), while younger patients are more often male and present more commonly with previous liver disease (especially related to alcohol) and cryptogenic PLA. Conclusion In patients aged 65 or older, PLA was more common in women and in those with a history of biliary disease, and E. coli was the most frequent bacterium. Mortality was also higher in the older group.